Enzymatic amperometric MWCNT-based biosensor - Noor Haslinda Abdullah. (2012)
An enzymatic, multi-walled carbon nanotube (MWCNT) - based biosensor is developed, with the knowledge of nanotechnology and electrochemistry, for a sensitive and reliable detection of glucose. The main motivation for the development of MWCNT - modified biosensor was the lack of solubility of MWCNT in most organic and inorganic solvents. Therefore, the potentials of MWCNT are explored due to its unique electrical and mechanical properties. The biosensor consists of platinum (Pt) electrode that was modified by coating different types of MWCNTs. Amperometry method was used to detect glucose by oxidizing it on the Pt electrode surface. The reagents used for the coatings were chosen for various reasons. MWCNTs were first tested due to their intrinsic nanostructure and high electrical conductivity. The properties of functionalized multi-walled carbon nanotube (MWCNT-COOH) were also explored due to its efficient dispersion. Both types of MWCNT were wrapped in Nafion, a perfluorosulfonated polymer, to form supramolecular complexes mainly by π-stacking with MWCNT surfaces. In this project, different techniques were used to characterize the dispersion of MWCNTs in glucose oxidase (GOx): Amperometry and Field Emission Scanning Electron Microscopy (FESEM). The influence of different experimental conditions: stirring speed, solvents and MWCNT-COOH, have an effect on the bio-catalytic activity of GOx on the Pt electrode.